What Role could Presence Play in the Practices of Academia? On the performativity of theory in the context of Performance Philosophy - Lagaay, Alice; Seitz, Anna (Revista Brasileira de Estudos da Presença, 2022)
The dialogue discusses the role presence could be permitted to play in academic situations of co-presence with others (in comparison to the importance of presence in artistic contexts). It ponders the extent to which conventional academic forms, quite apart from seeking to guarantee objectivity in theory, actually pre-determine, or in fact limit, the communicability of theoretical content. The conversation points to the need for a new dramaturgical attentiveness to the performativity of theory and calls for an innovative approach to the formats in which the questions and results concerning various fields in the humanities could be presented and negotiated more successfully.